Cadmium toxicity in nature generates the cancerous problems - Muhammad Qasim, Ali; Deb, Apu; Hasan, Md, Shanzid; Rahman, Masudur; Rahman, Habibur; Afrin, Sadia; Bhuiyan, Md. Khaledur Rahman; Roy, Uthpallkumar; Burhan Uddin, Mohammad; Mudhafar, Mustafa; Syrmos, Nokolas; Ahmed Mahedi, Md. Rezwan (EM International, 2022)
A naturally occurring metal, cadmium is noticed in tiny amounts in a variety of sources such as food, water, soil, and the atmosphere. Cadmium may be edified in all soils and rocks, including coal and mineral fertilizers. In general, non-smoker people are getting affected by food contamination. The main theme of this paper is cancer activity by cadmium pollution of our environment. Foods are getting contaminated by industrial wastes. Wastes have Cd2+ ions which can bind with plant materials and also bind with animal muscles. On the other hand, the smoker people take the cadmium by smoking tobacco. The cadmium can easily bind up with the organs like the lung, prostate, breast, bone, etc. When industrial wastes are thrown into rivers, ponds, or open spaces, particularly in South Asian nations, the water becomes poisoned and the soil becomes deteriorated; as a result, the environment becomes more hazardous. In consequence, people can be oppressed by significant sicknesses that occurred by Cd2+, such as osteoporosis, renal dysfunction, anemia, alveolar malignancy, and also other conditions.